Food policy measures in response to COVID-19 in Central Asia and the Caucasus: Taking stock after the first year of the pandemic - Nodir Djanibekov; Thomas Herzfeld; Pedro Marcelo Arias (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2021)
Despite initial concerns of catastrophic outcomes, the COVID-19 pandemic and the resulting lockdown measures did not severely affect regional agriculture in Central Asia and the Caucasus. They did, however, affect food supply chains in terms of demand and logistics. Food prices were volatile throughout 2020 and particularly high in countries with currency depreciation. However, the on-going COVID-19 pandemic as a human and health crisis presents an ever increasing risk to the economies of Central Asia and the Caucasus. The global implications of the pandemic, combined with a decline in oil and gas exports and migrant remittances, could impede recovery and undermine economic stability in the region. Policymakers should avoid disrupting domestic food supply chains and placing barriers to trade through export bans and quotas. At the same time, they must ensure food security and reduced price volatility through diversified trade networks. Deeper domestic value chains and efficient management of public and private food stock reserves will better prepare countries to face the continuing effects of the COVID-19 pandemic. Better-informed and targeted policy responses to a pandemic require improved national systems of nutrition research and monitoring, and timely availability of data not only relating to production but also to other levels of the agrifood chain.
urn:nbn:de:gbv:3:2-146459
Keywords: 330; Ernährungssicherung; Ernährungspolitik; Coronavirus; Zentralasien; Kaukasus